Hubungan Tingkat Pengetahuan Ibu dengan Pemberian ASI Eksklusif pada Bayi 0-6 Bulan di Puskesmas Motoboi Kecil - Akbar, Hairil; Nurul Hikma Saleh, Sitti; Muzayyana; Agustin (Journal of Health Education and Literacy, 2021)
Introduction: Based on the results of nutritional status monitoring conducted in Indonesia in 2017, the exclusive breastfeeding coverage was 35.7%. The annual report data of the Motoboi Kecil Health Center, South Kotamobagu District in 2020, the exclusive breastfeeding coverage in 2017, 2018, and 2019 were 80.0%, 83.8%, and 75.7% respectively. Exclusive breastfeeding is breastfeeding without additional food provided for infants aged 0 to 6 months. The purpose of this study was to analyze the relationship between maternal knowledge and exclusive breastfeeding for infants 0-6 months at the Motoboi Kecil Health Center. Method: This study applied an observational study with a cross-sectional study design. The study population was all mothers with infants aged 0-6 months in the working area of Motoboi Kecil Health Center, with a total of 169 individuals and a sample size of 60. The sampling technique used simple random sampling. The variables were maternal knowledge and exclusive breastfeeding. The statistical test was carried out using the chi-square test. Results: The study showed that the level of maternal knowledge was associated with exclusive breastfeeding for infants 0-6 months at the Motoboi Kecil Health Center with a p-value = 0.004. Conclusion: There is a relationship between the level of maternal knowledge and exclusive breastfeeding. It is advised that the mothers increase their knowledge so that they can provide exclusive breastfeeding for their infants.